2011
DOI: 10.1038/oby.2011.29
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Lipid Synthesis in Small Rat Adipocytes by Microvesicle‐Associated CD73 From Large Adipocytes

Abstract: Filling‐up lipid stores is critical for size increase of mammalian adipocytes. The glycosylphosphatidylinositol (GPI)‐anchored protein, CD73, is released from adipocytes into microvesicles in response to the lipogenic stimuli, palmitate, the antidiabetic sulfonylurea drug glimepiride, phosphoinositolglycans (PIG), and H2O2. Upon incubation of microvesicles with adipocytes, CD73 is translocated to cytoplasmic lipid droplets (LD) and esterification is upregulated. The role of CD73‐harboring microvesicles in coor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 64 publications
(129 reference statements)
1
28
0
Order By: Relevance
“…Proteomic profiling studies of EVs released by adipocyte cell models have been documented including that of hypoxic 3T3‐L1 cells and of animal models of obesity and diabetes but to date not much information is available for circulating EVs in human obesity. Available literature from in vitro systems suggests that EVs from adipocytes contain protein and RNA species involved in regulating lipid metabolism and adipokine production …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomic profiling studies of EVs released by adipocyte cell models have been documented including that of hypoxic 3T3‐L1 cells and of animal models of obesity and diabetes but to date not much information is available for circulating EVs in human obesity. Available literature from in vitro systems suggests that EVs from adipocytes contain protein and RNA species involved in regulating lipid metabolism and adipokine production …”
Section: Discussionmentioning
confidence: 99%
“…Adipocytes have been shown to produce EVs of heterogeneous sizes which contribute to regulate lipid deposition and angiogenesis, reviewed in . Deng et al .…”
Section: Introductionmentioning
confidence: 99%
“…For the moment, the exact nature and physiological role of this novel adipocyte population are still misunderstood, but these results suggest they may be implicated in the metabolic dysfunction of white adipose tissues associated with ectopic fat accumulation, as shown by the presence of hepatic steatosis [64]. A recent study suggests a molecular cross-talk between larger adipocytes and these small adipocytes that regulates the fatty acid uptake capacity of the latter [66].…”
Section: Molecular and Cellular Basis For Adipose Tissue Metabolic Dysfmentioning
confidence: 95%
“…This would explain the increase of PTRF and caveolin-1 over time in adipocytes treated with rPTRF. Muller et al reported that adipocytes can enlarge when treated with certain EV [14] which triggered the expression of some adipogenic genes among which are regulators of caveola expression [19]. We hypothesize that the larger size of the adipocytes treated with rPTRF may be explained by an increased number of caveolae, thus allowing the adipocyte to have a membrane reservoir to rapidly increase cell surface.…”
Section: Discussionmentioning
confidence: 90%